Contribution of Membrane Lipids to Postsynaptic Protein Organization - Westra, Manon; Gutierrez, Yolanda; MacGillavry, Harold D. (Frontiers in Synaptic Neuroscience, 2021)
The precise subsynaptic organization of proteins at the postsynaptic membrane controls synaptic transmission. In particular, postsynaptic receptor complexes are concentrated in distinct membrane nanodomains to optimize synaptic signaling. However, despite the clear functional relevance of subsynaptic receptor organization to synaptic transmission and plasticity, the mechanisms that underlie the nanoscale organization of the postsynaptic membrane remain elusive. Over the last decades, the field has predominantly focused on the role of protein-protein interactions in receptor trafficking and positioning in the synaptic membrane. In contrast, the contribution of lipids, the principal constituents of the membrane, to receptor positioning at the synapse remains poorly understood. Nevertheless, there is compelling evidence that the synaptic membrane is enriched in specific lipid species and that deregulation of lipid homeostasis in neurons severely affects synaptic functioning. In this review we focus on how lipids are organized at the synaptic membrane, with special emphasis on how current models of membrane organization could contribute to protein distribution at the synapse and synaptic transmission. Finally, we will present an outlook on how novel technical developments could be applied to study the dynamic interplay between lipids and proteins at the postsynaptic membrane.